Surface modification, characterization and properties of regenerated cellulose NYPA fructicans filled microcrystalline cellulose biocomposite films - Govindan, Vaniespree (School of Materials Engineering, 2017)
In present work, RC biocomposite films were prepared by solvent casting method. Tensile properties such as tensile strength, elongation at break and Young's modulus of RC biocomposite films were investigated. X-ray diffraction (XRD) was used to measure the crystallinity of the RC biocomposite films. The morphology study of composites was carried out using scanning electron microscope (SEM) in order to examine filler-matrix interaction and filler dispersion. The thermal properties of RC biocomposite films were analyzed using thermogravimetric analysis (TGA). The functional groups of the RC biocomposite films were identify using Fourier transform infrared (FTIR). Moisture content and biodegradation methods were used to measure the moisture uptake and biodegradability of the RC biocomposite films.